Simulated mutagenesis to predict the mutational effect on the thermostability of Bacillus circulans xylanase - Abdul Hadi, Muaz; Noorbatcha, Ibrahim Ali; Ismail, Ahmad Faris; Mohd. Salleh, Hamzah (Research Journal of Chemistry and Environment, 2010)
Due to the environmental concerns, the use of hemicellulolytic enzymes has recently attracted considerable interest as a substitute for chlorine chemicals in pulp bleaching. The challenges in incorporating enzyme to the bleaching system are to have a stable and active xylanase at high temperatures. To date, numerous factors have been considered for putative determinants of protein thermostability. Yet, there is no universal theory or rule to explain the principles underlying protein thermostability, as thermostability appears to be interplayed by many factors. In this work we have used computational methods to analyze the structural factors responsible for the themostability of Bacillus circulans xylanase which have been identified as one of the promising xylanase source to treat the pulp before bleaching it through the conventional bleaching sequences. Simulated point mutation shows that arginine substitution potentially increased the number of hydrogen bond; correlate with the xylanase activity and some changes in amino acid sequence specifically to the α-helix and β-sheet appeared to be promising in improving thermostability of xylanase together with some changes in salt bridges and accessible surface. This in silico method results can be used to develop new efficient xylanase for pulp bleaching industry.